Navigating queerness and religion in India: a phenomenological queer ethnography - Sharma, Karan (Religion, 2026)
This article inquires into the complex intercourse of religion and sexuality within queer life-worlds. Involving a phenomenological queer ethnography with thirty-eight queer subjects from different regions and religious denominations in India, it unravels the varied perceptions of religious acceptance of queer gender-sexual identities and behaviors. Analyzing, primarily, the experiences of religion among Hindu, Muslim, and Christian queers and drawing from Saroglou's four dimensions of religion, the study reveals that belonging to a religious community is highly compromised among queers. Moreover, behavior and actions in accordance with religious morality vary widely; some queer individuals reconcile their queerness and religion, while others reimagine, reinterpret, or even discard religious tenets, or overcome their sexuality to grow closer to God(s). This analysis underscores how queer individuals navigate their queerness within religious contexts through varied modes of negotiating between their gender-sexual subjectivity and heteronormative religious moralities.